2023
DOI: 10.3390/pharmaceutics15041257
|View full text |Cite
|
Sign up to set email alerts
|

Living Cells and Cell-Derived Vesicles: A Trojan Horse Technique for Brain Delivery

Abstract: Brain diseases remain a significant global healthcare burden. Conventional pharmacological therapy for brain diseases encounters huge challenges because of the blood–brain barrier (BBB) limiting the delivery of therapeutics into the brain parenchyma. To address this issue, researchers have explored various types of drug delivery systems. Cells and cell derivatives have attracted increasing interest as “Trojan horse” delivery systems for brain diseases, owing to their superior biocompatibility, low immunogenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 155 publications
0
3
0
Order By: Relevance
“…Here, nanoparticles enter the bloodstream first and then navigate through the selective BBB, with engineered nanoparticles potentially accessing the brain. Cells themselves may carry nanomaterials through the BBB, becoming an important traffic route to the CNS for being considered (Ou et al, 2023). Nanoparticles can travel along nerve fibers, like the olfactory nerve, reaching deeper brain regions post-exposure.…”
Section: B Lood-b R Ain Barriermentioning
confidence: 99%
“…Here, nanoparticles enter the bloodstream first and then navigate through the selective BBB, with engineered nanoparticles potentially accessing the brain. Cells themselves may carry nanomaterials through the BBB, becoming an important traffic route to the CNS for being considered (Ou et al, 2023). Nanoparticles can travel along nerve fibers, like the olfactory nerve, reaching deeper brain regions post-exposure.…”
Section: B Lood-b R Ain Barriermentioning
confidence: 99%
“…Various kinds of cells showed diverse dose–response curves for the cell viability after the exposure of CIONPs. Majeed and Ou et al [ 25 , 26 ] observed in guinea pigs that CIONPs induce respiratory problems. Hadrup and Ansari et al [ 27 , 28 ] reported that CIONPs cause micronuclei to develop in human peripheral lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study investigated the biocompatibility of CIONPs and their adverse effects on different organs, such as the kidneys, liver, spleen, heart, and brain of rabbits ( Oryctolagus cuniculus ). The CIONPs were injected into the rabbits following the previous experimental protocol [ 19 , 26 ] for hematological, serum biochemical, and histopathology of selected organs of the controlled and treated rabbits.…”
Section: Introductionmentioning
confidence: 99%